Urgensi Keluarga Sakinah sebagai Fondasi Rumah Tangga Perspektif Fikih dan Hukum Positif - Fauziyah, Ita Marifatul (Institut Agama Islam Negeri (IAIN) Kediri, 2024)
A harmonious family (sakinah) is an important foundation for the realization of a harmonious and happy household. From a fiqh (Islamic jurisprudence) perspective, a sakinah family is defined as a family built based on piety towards Allah SWT, mutual respect and affection among family members, and the ability to properly practice Islamic law. This concept is not only discussed from a fiqh perspective but is also recognized in Indonesian positive law, where a sakinah family is defined as a family capable of living harmoniously and prosperously, with strong resilience in facing various challenges. This research aims to examine the urgency of a sakinah family as the foundation of a household from the perspectives of fiqh and positive law. The approach method used in this research is a conceptual approach. Researchers try to understand and explain the concepts and principles of Islamic law by analysing and understanding Islamic legal texts, as well as studying the urgency of a sakinah family as the foundation of the household. The results show that a sakinah family plays a vital role in building a harmonious and happy household. A sakinah family becomes a solid foundation for the realization of a quality and virtuous future generation. This research also shows that fiqh and positive law share similarities in viewing the urgency of a sakinah family. Both emphasize the importance of building a family based on piety towards Allah SWT, mutual respect and affection among family members, and the ability to properly practice Islamic law. However, there are some differences in the approaches of fiqh and positive law in realizing a sakinah family. Fiqh emphasizes spiritual and moral aspects, while positive law emphasizes legal and regulatory aspects.